2011
DOI: 10.1158/0008-5472.can-10-3666
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-205 Inhibits Src-Mediated Oncogenic Pathways in Renal Cancer

Abstract: The Src family of protein kinases (SFKs) plays key roles in regulating fundamental cellular processes, including cell growth, differentiation, cell shape, migration and survival, and specialized cell signals in various malignancies. The pleotropic functions of SFKs in cancer make them promising targets for intervention. Here we sought to investigate the role of miR-205 in inhibition of Src-mediated oncogenic pathways in renal cancer. We report that expression of miR-205 was significantly suppressed in renal ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 47 publications
3
105
1
3
Order By: Relevance
“…miRNAs are known to contribute to multiple tumorigenic steps in human cancers, including RCC. Recent studies have identified regulatory activities of miRNAs in ccRCC cell growth (4)(5)(6)(7)(8), apoptosis (5,6,8,9), migration, and invasion (5)(6)(7)(8). A predominant and systemic alteration in miRNA expression during renal carcinogenesis has been indicated by present studies of miRNA expression profiling (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 73%
“…miRNAs are known to contribute to multiple tumorigenic steps in human cancers, including RCC. Recent studies have identified regulatory activities of miRNAs in ccRCC cell growth (4)(5)(6)(7)(8), apoptosis (5,6,8,9), migration, and invasion (5)(6)(7)(8). A predominant and systemic alteration in miRNA expression during renal carcinogenesis has been indicated by present studies of miRNA expression profiling (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 73%
“…Additional targets of miR-205 identified in other tissue types have not been validated in breast cancer. [83][84][85][86] Likely, miR-205 plays a role in specific pathways in tumorigenesis and tumor progression in a cell type-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…miR-205 is upregulated compared with normal tissues in transitional cell carcinoma of the bladder; 42,43 squamous cell carcinoma of the uterine cervix; 44 endometrial adenocarcinomas, including the endometrioid 45 and serous 46 types; ovarian endometrioid adenocarcinoma; 47 and nonsmall cell carcinomas (adenocarcinoma and squamous cell carcinoma) of the lung. 48 In contrast, miR-205 is downregulated in breast carcinomas; 49,50 adenocarcinoma of the prostate; 51,52 renal cell carcinoma; 53 and spindle cell carcinomas of the head and neck. 54 This apparent disparity of function likely reflects the molecular plasticity of miR-205 as a regulator of multiple different gene targets, which would exert potentially pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%